Inflammation and cancer - Mierke, Claudia (Physics of Cancer, 2018)
The link between inflammation and cancer has been proposed a long time ago and inflammation is now a major part of current cancer research. The analysis of the biophysical parameters or the determination of the prerequisites for inflammation belong to a still growing and newly emerging research field of physical tumor-immunology, which will probably set a novel future focus in the physics of cancer field. Inflammation, especially chronic inflammation, possesses pro-tumorigenic effects and it therefore increases the probability of promoting various tumor growths and the further progression of cancer. The impact of inflammation on the metastatic potential of tumors is not yet well known. It has been hypothesized that the transendothelial migration process leading to cancer metastasis is affected by inflammatory cytokines and the associated mechanical microenvironmental changes. However, the impact of acute and chronic inflammatory processes on cancer progression is still elusive, although it has been seen that the success of cancer therapy depends on the associated inflammatory processes involved in cancer disease. The mechanical properties of the tumor surrounding stroma may also change during these inflammatory processes and subsequently alter the tumorigenic potential of distinct cancer cell types or cancer cell subpopulations. However, this is not yet well known and it requires extensive future research efforts. In this chapter, the principal cellular and molecular pathways promoting tumor progression and inhibiting tumor progression are presented and discussed in the context of inflammation. Finally, the interplay between cancer and inflammation is highlighted throughout the chapter.
CRIS-Team WoS Importer:2019-08-27